Aeroelastic Tailoring of the Next Generation Civil Tiltrotor Technological Demonstrator Composite Wing - Aniello Daniele Marano; Marika Belardo; Jacopo Beretta; Filomena Starace; Salvatore Orlando; Claudio Punzi; Raffaele Frajese; Nicola Paletta; Luigi Di Palma (Aerospace, 2022)
The tiltrotor wing structure is one of the most critical and heavily investigated structures in design due to the fundamental need to consider the interactions between the wing, pylon, and rotor systems to achieve aircraft aeroelastic stability. Indeed, in high-speed forward flight, wing flexural and torsional stiffness have fundamental roles in pitch-whirl stability. Another specific concern of tiltrotors is dynamic mode placement; it is necessary to properly place wing bending modes away from prop-rotor forcing frequencies. The main aeroelastic stability and dynamics requirements and the wing design process flow for the next generation civil tiltrotor are presented in this work. In this context, the use of composite materials plays a fundamental role in the attempt to satisfy the requirements, with the perpetual aim of minimizing the structural weight. An overview of the idealized and adopted models for strength, aeroelasticity, and whirl flutter analysis is provided. The primary focus was on the aeroelastic tailoring process. To satisfy, at the same time, all of the structural dynamic and aeroelastic stability requirements, the best compromise, with an acceptable weight penalty, was the mixture of two methodological solutions: adding unidirectional tape in the zones of the upper and lower skins for flexural out-of-plane frequency and adding a proper number of ±45° fabric layers at the locations of the skin with the highest value of strain energy for in-plane torsional modes. The results show that the proposed method based on modal strain energy analysis enables a tiltrotor aeroelastic tailored wing design. It can be easily employed in similar applications (e.g., vehicle scale-up/down) with the advantage of using the stiffness requirements derived directly from the aeroelastic ones (i.e., structural frequencies). The specific wing achieved aeroelastic clearance by adding only 2.7% of extra mass.